Effects of different fatigue levels on physiological responses and pacing in judo matches - Franchini, E.; Takito, M. Y.; Alves, E. D.; Shiroma, S. A.; Julio, U. F.; Humberstone, C. (The Journal of Strength and Conditioning Research, 2019)
The objective of this study was to compare athletes' pacing during judo match simulation between different fatigue states. Twelve judo athletes (30.2 ± 3.2 years old, 85.6 ± 10.8 kg, 181.0 ± 5.7 cm, 19 ± 7 years of judo experience) completed three 4-minute matches against the same opponents, at 15-minute intervals in 3 different conditions: after warm-up (Control; C); after a regular training session (totaling 90 minutes); after a high-intensity interval exercise (2 blocks of 10 sets of 20-second all-out uchi-komi, with 10-second interval between sets and 5-minute interval between blocks). All matches were mediated according to the official rules, filmed, and analyzed concerning: rating of perceived recovery (RPR), rating of perceived exertion (RPE), heart rate (before and after match), blood lactate concentrations [La] before, peak after match and delta (peak minus the prematch values), and time-motion measures (frequencies and durations of actions). Time-motion measures included athlete displacement without contact, gripping, attack, feint, groundwork combat, pauses, and high- to low-intensity effort ratio. The experimental conditions resulted in different physiological and perceived responses prematch (HR, [La], RPR) and postmatch simulations (HR and [La]peak), with no change in RPE and few changes in technical variables. There was a decrease in grip dispute time, and increase in time of displacement without contact. These technical changes were enough to preserve the pace during the matches, which seemed to be controlled by the athletes to maintain their number of attacks, feints, and RPE.